Disseminated intravascular coagulation in meningococcal sepsis - Zeerleder, S.; Zenklusen, R. Zürcher; Hack, C. E.; Wuillemin, W. A. (Hämostaseologie, 2003)
We report on a man (age: 49 years), who died from severe meningococcal sepsis with disseminated intravascular coagulation (DIC), multiple organ dysfunction syndrome and extended skin necrosis. We discuss in detail the pathophysiology of the activation of coagulation and fibrinolysis during sepsis. The article discusses new therapeutic concepts in the treatment of disseminated intravascular coagulation in meningococcal sepsis, too.
Keywords: DIC; MODS; sepsis